The Earnings Management Strategy of List Companies in Pearl River Delta Region of China Based on Complex Network Theory. (10th December 2020) - Zhao, Run-Hua; Cheng, Jie; Xu, Nai-Ru
Abstract : This paper aims to detect the methods of earnings management in Pearl River Delta region of China. The data were selected based on the list companies of Pearl River Delta region from 2008 to 2019 and the balanced panel analysis was adopted to pursue the results. After the random effect analysis, this study reaches the conclusion that downward earnings is through total assets, the difference between sales and receivables, fixed assets, and sales and upward earnings is mainly through the changes of sales by the companies in Pearl River Delta region of China.